Relationship between geology and landslide occurrence in the Sor Range, Quetta, Pakistan - Khan, Abdul Tawab (Journal of Nepal Geological Society, 2004)
The Sor Range is situated about 16 km east of Quetta in the axial zone west of the Sulaiman Thrust- Fold Belt. It contains sedimentary rocks ranging in age from Jurassic to Recent. The Ghazij Formation of Early Eocene is divided into the Lower, Middle, and Upper Members, respectively. The Kirthar Formation of Late Eocene age is divided into the Habib Rahi Limestone and Serki Member. The Siwaliks of Miocene to Pleistocene age consist of the Nagri, Dhok Pathan, and Soan Formation (Urak conglomerate) and are overlying the Kirthar Formation with an unconformity. Landslide susceptibility mapping was carried out on a scale of 1:50,000. This study describes various ancient and active landslides in the area and fissures developed in the Ghazij Formation that cover an area of about 130,000 m2. There are also several hundred metres long and very wide fissures in the dip slope of the Kirthar Formation. The widespread instabilities are confined to the fold belts as well as major wrench and thrust faults, and they were triggered or reactivated by earthquakes.